Evaluation and impact factors of Doppler wind lidar during Super Typhoon Lekima (2019). (March 2023) - Tang, Shengming; Guo, Yun; Wang, Xu; Zhu, Rong; Tang, Jie; Zhang, Shuai
Abstract: Doppler wind lidar (DWL) has been widely employed in the wind energy industry. However, the evaluation of DWL winds under typhoon conditions is still rare. This study evaluated the accuracy of wind data measured by two types of DWLs (WindPrint S4000 and WindCube V2), and investigated the impact of three environmental factors (precipitation intensity, relative humidity and drift distance of sounding balloons) on the DWL-measured wind speed and direction. Data were collected from the joint observation at Baoshan, Zhoushan and Taizhou during the passage of Super Typhoon Lekima in 2019. The DWL observations were compared with measured data from balloon-borne radiosonde released at the same location. The results show that the optimal agreement was found with the 1-min average DWL-measured winds. The DWL data missing rate decreases with the increase of signal-to-noise ratio and height from the surface. The applicability of DWL is poor when the precipitation intensity is larger than 50 mm h −1 . The DWL wind speed and wind direction biases significantly increase when the relative humidity exceeds 85% and 90%, respectively. Moreover, the measured wind data of the balloon-borne radiosonde are not reliable when the horizontal drift distance is larger than 2 km.